2017
DOI: 10.18054/pb.v119i1.4386
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of madecassoside - a major component of centelloside - in centella (Centella asiatica (L.) Urban) cells elicited by salicylic acid

Abstract: Background and Purpose: Use of elicitors is one of the most important methods to increase the production of secondary metabolites in plants. Salicylic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…In particular, inoculum size had a positive effect on biomass and metabolite production up to an optimum concentration 28 . In this study, the optimal inoculum size for biomass accumulation and gypenoside production was 3 g of callus per 50 ml culture medium (6% w/v ), which is similar to that reported by Loc et al for the production of madecassoside in Centella asiatica (L.) suspension cell culture 29 . Nhan et al also found that an inoculum size of 6% ( w/v ) is optimal for eurycomanone biosynthesis in long jack ( Eurycoma longifolia ) suspension cells culture 24 .…”
Section: Discussionsupporting
confidence: 85%
“…In particular, inoculum size had a positive effect on biomass and metabolite production up to an optimum concentration 28 . In this study, the optimal inoculum size for biomass accumulation and gypenoside production was 3 g of callus per 50 ml culture medium (6% w/v ), which is similar to that reported by Loc et al for the production of madecassoside in Centella asiatica (L.) suspension cell culture 29 . Nhan et al also found that an inoculum size of 6% ( w/v ) is optimal for eurycomanone biosynthesis in long jack ( Eurycoma longifolia ) suspension cells culture 24 .…”
Section: Discussionsupporting
confidence: 85%
“…We investigated the differential expression of genes involved in triterpenoid pathway as well as of miRNAs in SA augmented, in vitro grown cultures of C. asiatica. SA is a potent elicitor for increasing triterpenoid content in C. asiatica as many workers have experimentally proved it multiple times [87][88][89][90]. This could provide an indication whether effects of SA on centelloside biosynthesis could be mediated by changes in miRNAs.…”
Section: Discussionmentioning
confidence: 98%
“…Elicitation was performed with 1 µM of coronatine (COR) and 150 µM of salicylic acid (SA) (Sigma Aldrich, St. Louis, MO, USA), which were previously filter-sterilized and added to the cell suspensions. The SA concentration was selected based on Loc et al [ 56 ] and Alcalde et al [ 27 ] studies.…”
Section: Methodsmentioning
confidence: 99%